Pyrazine‐Functionalized Donor–Acceptor Covalent Organic Frameworks for Enhanced Photocatalytic H2 Evolution with High Proton Transport - Wang, Feng‐Dong; Yang, Li‐Juan; Wang, Xin‐Xin; Rong, Yi; Yang, Li‐Bin; Zhang, Chen‐Xi; Yan, Fang‐You; Wang, Qing‐Lun (Small (Weinheim an der Bergstrasse, Germany), 2023)
The well‐defined 2D or 3D structure of covalent organic frameworks (COFs) makes it have great potential in photoelectric conversion and ions conduction fields. Herein, a new donor–accepter (D–A) COF material, named PyPz‐COF, constructed from electron donor 4,4′,4″,4′″‐(pyrene‐1,3,6,8‐tetrayl)tetraaniline and electron accepter 4,4′‐(pyrazine‐2,5‐diyl)dibenzaldehyde with an ordered and stable π‐conjugated structure is reported. Interestingly, the introduction of pyrazine ring endows the PyPz‐COF a distinct optical, electrochemical, charge‐transfer properties, and also brings plentiful CN groups that enrich the proton by hydrogen bonds to enhance the photocatalysis performance. Thus, PyPz‐COF exhibits a significantly improved photocatalytic hydrogen generation performance up to 7542 µmol g−1 h−1 with Pt as cocatalyst, also in clear contrast to that of PyTp‐COF without pyrazine introduction (1714 µmol g−1 h−1). Moreover, the abundant nitrogen sites of the pyrazine ring and the well‐defined 1D nanochannels enable the as‐prepared COFs to immobilize H3PO4 proton carriers in COFs through hydrogen bond confinement. The resulting material has an impressive proton conduction up to 8.10 × 10−2 S cm−1 at 353 K, 98% RH. This work will inspire the design and synthesis of COF‐based materials with both efficient photocatalysis and proton conduction performance in the future. The introduction of a pyrazine into the synthesized donor–accepter covalent organic frameworks achieves an enhanced electron push–pull effect and narrower bandgap, thereby promoting internal charge transfer for higher photocatalytic hydrogen production performance. Meanwhile, the abundant N sites of pyrazine further anchor the phosphoric acid proton carriers to achieve high proton conductivity.